2012
DOI: 10.3892/ol.2012.822
|View full text |Cite
|
Sign up to set email alerts
|

The expression and clinical significance of PI3K, pAkt and VEGF in colon cancer

Abstract: Abstract. Background PI3K/Akt signaling has been shown to be activated in a variety of cancers. However, the correlation between Akt activation and VEGF expression is unclear in colon cancer tissues. This study aimed to investigate the expression and predictive value of phosphorylated Akt (pAkt) and VEGF in colon cancer tissues. The expression of PI3K, pAkt and VEGF was detected by immunohistochemical staining in 60 samples of colon cancer tissues and their corresponding adjacent normal colon tissues. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Subsequently, analysis of the influence of miR-29c on NSCLC cell activities demonstrated that overexpression of miR-29c was able to inhibit the proliferation and promote the apoptosis of NSCLC cells. Since high expression of VEGFA has been reported to be correlated with the proliferation and metastasis of various types of tumor (11), it was hypothesized that miR-29c may regulate NSCLC cell activities by targeting VEGFA. Through bioinformatics analysis, it was predicted that VEGFA may be a direct target for miR-29c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, analysis of the influence of miR-29c on NSCLC cell activities demonstrated that overexpression of miR-29c was able to inhibit the proliferation and promote the apoptosis of NSCLC cells. Since high expression of VEGFA has been reported to be correlated with the proliferation and metastasis of various types of tumor (11), it was hypothesized that miR-29c may regulate NSCLC cell activities by targeting VEGFA. Through bioinformatics analysis, it was predicted that VEGFA may be a direct target for miR-29c.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary factors in tumor angiogenesis stimulation is vascular endothelial growth factor A (VEGFA) (10). According to previous research, high expression of VEGF is associated with the proliferation and metastasis of several types of cancer (11). Through bioinformatics methods, it was identified that VEGFA may be a gene target for miR-29c.…”
Section: Introductionmentioning
confidence: 99%
“…This model is in agreement with recent clinical studies reporting that PI3K and pAkt are highly expressed in colon cancer tissues. 31 IGF ligands and IGF1Rs are expressed in most, if not all, tissues in mammals and in zebrafish. 32,33 How is the ubiquitous IGF signaling system activated exclusively in NaR cells under low [Ca 2 Ăľ ] environments?…”
Section: Discussionmentioning
confidence: 99%
“…VEGF (vascular endothelial growth factor), as a major pro-angiogenic factor in tumor tissues, can directly stimulate the proliferation of endothelial cells by specific receptors on them, to produce the plasminogen activator and collagenase, etc., increase vascular permeability, and promote plasma fibrinogen extravasation. This can not only promote the migration of endothelial cells, helping angiogenesis, but also be conducive to tumor cell shedding, invasion or diffusion to adjacent matrix of fibrous and connective tissues, so as to create the conditions for tumor invasion and metastasis [19][20][21]. Colon cancer is a malignant tumor with rich blood supply and high metastasis, and its tumor angiogenesis, proliferation, invasion and metastasis are closely related to VEGF [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%